2012
DOI: 10.5861/ijrsll.2012.154
|View full text |Cite
|
Sign up to set email alerts
|

Literature stance in developing critical thinking: A pedagogical look

Abstract: Students in literature classes are expected to think critically and apply their critical and analytical skills to the texts they study. As to the writers, the factors counted by some scholars (e.g. Topping, 1968) as the demerits of the employment of literature in EFL/ESL classes including difficulty level of vocabulary, structural complexity, non-normative use of language, and even remote cultural perspectives are neither persuasive nor logical, but are exactly what can be employed to enrich language learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In addition, Zengin & Yükselir (2019) point out that literature inspires learners to think over tender or beautiful features of life and enhances their vocabulary and improves their sense of literary appreciation. Kaya (2018), and Khatib & Shakouri (2013) confirm that learners who do not know the aims of studying literature are likely to lose the sense of pleasure and enjoyment that goes with the study of literature. Accordingly, analysis and discussion of the results gleaned from the first and fourth domains Difficulties of Studying Literature" and "Employment Opportunities" provide the answer to the second research question "What are the cognitive beliefs that hinder learners' willingness to study English literature?…”
Section: Analysis Of Students' Cognitive Beliefs About Learning Englimentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, Zengin & Yükselir (2019) point out that literature inspires learners to think over tender or beautiful features of life and enhances their vocabulary and improves their sense of literary appreciation. Kaya (2018), and Khatib & Shakouri (2013) confirm that learners who do not know the aims of studying literature are likely to lose the sense of pleasure and enjoyment that goes with the study of literature. Accordingly, analysis and discussion of the results gleaned from the first and fourth domains Difficulties of Studying Literature" and "Employment Opportunities" provide the answer to the second research question "What are the cognitive beliefs that hinder learners' willingness to study English literature?…”
Section: Analysis Of Students' Cognitive Beliefs About Learning Englimentioning
confidence: 97%
“…Literature is also useful in the process of learning the general and private customs and traditions of a society and individuals. At the educational level, Khatib & Shakouri (2013) believe that English Literature can serve as the source of correlation between the students` proficiency and language use. Relevantly, Hussein & Al-Emami (2016) explain that both language and literature are interrelated parts of English, and each is described as one side of a coin.…”
Section: The Influence Of Literature On English Language Learningmentioning
confidence: 99%
“…As Shelley (1989, cited in Khatib & Shakouri, 2013 put it, literature is the expression of imagination. Cownway (1996, in Khatib & Shakouri, 2013) also asserted imagination forms bridges between existence and perception, between perception and expression. Since the nature of literature in general is to engage readers intellectually in the literary works, it is thought that literary novels and stories can provide students with some opportunities to employ such critical thinking skills as analyzing, judging, synthesizing, evaluating, and thinking logically.…”
Section: Literature-based Reading and Developing Critical Thinking Skmentioning
confidence: 99%
“…Furthermore, they indicated that higher order thinking skills could enhance ESL learners' writing ability and interest in ESL writing lessons. Khatib and Shakouri (2012) proposed that critical thinking could be developed through literature reading. They claimed that its cultural load, structural complexity and non-normative use of language as claimed, is exactly what can be employed to enrich language teaching and learning experiences, and enhance critical thinking (p.…”
Section: International Journal Of Research Studies In Language Learnimentioning
confidence: 99%